The Influence of Environmental Components on Student Learning Outcomes in Economics Subjects at Banda Aceh City High School - Hidayat*, Syarif; Jaya, Alfi Syahril Fuadi; Zulfadhli, Zulfadhli (Riwayat: Educational Journal of History and Humanities, 2023)
Environmental factors have a very potential influence on the learningprocess in order to get good learning outcomes. Of the many environmentalfactors, it can be divided into 6 factors, namely these factors are politics, socio-culture,security,economy,religion,andnature.Thisstudyaimstodeterminetheeffect of environmental components on student learning outcomes in economicssubjects at SMA Kota Banda Aceh. This study uses a quantitative method withexplanatory research. The population in this study were all high school studentsin Banda Aceh City at 6 high schools in Banda Aceh City, namely 60 students. Thesampling technique in this study used a stratified random sampling technique orrandom sampling. Data collection was carried out by observing and distributingquestionnaires. Dataanalysis used validitytest,reliability test, simple linearregression test, coefficient of determination test (R-Squared) and hypothesistesting.